Conversational topics discussed by individuals with severe traumatic brain injury and their communication partners during sub-acute recovery. (18th September 2016) - Brassel, Sophie; Kenny, Belinda; Power, Emma; Elbourn, Elise; McDonald, Skye; Tate, Robyn; MacWhinney, Brian; Turkstra, Lyn; Holland, Audrey; Togher, Leanne
Abstract: Primary objective : To investigate the nature and patterns of conversational topics discussed by individuals with severe TBI and familiar communication partners at 3 and 6 months post-injury, and to examine changes occurring in conversational topics during sub-acute recovery. Research design : Qualitative content analysis was used to explore the nature of topics and generate conversational themes. Topic analysis provided an understanding of conversational topic management by identifying patterns of topic initiation and maintenance. Methods : Twenty-two people with severe TBI and a familiar communication partner engaged in a 10-minute casual conversation on self-selected topics at 3 and 6 months post-injury. Main outcomes and results : Three main conversational themes were identified: connecting; re-engaging; and impacts of injury. The nature of topics related to these themes changed over time to reflect participants' sub-acute rehabilitation experiences. Most conversational dyads maintained similar conversational and topic patterns during sub-acute recovery. Conclusions : Qualitative analysis provides a new insight into the conversational topics of individuals with severe TBI. Many participants engaged in appropriate conversations and discussed mutually important topics with familiar communication partners. Findings may inform speech-language pathology intervention in sub-acute recovery to improve conversational discourse abilities of individuals with severe TBI and support their communication partners.